Will China's three-child policy defuse the demographic time bomb? - Britta Kuhn; Thomas Neusius (RheinMain University of Applied Sciences, Wiesbaden Institute of Finance and Insurance (wifin), 2022)
China is undergoing a particularly fast demographic transition. Accelerated through decades of political restrictions on family planning, the median age is rising and there is a growing share of retirees, while labour force potential is declining. Faced with dire consequences for both economic growth and wealth distribution, the government has gradually relaxed its one-child policy. Will this policy shift succeed? Our study simulates China's old-age dependency ratio and total dependency ratio until the end of the century, assuming total fertility rates between 1.0 and 2.0 with constant and increasing life expectancy. It shows that both ratios would substantially increase even in the best case. Therefore, China urgently needs reforms beyond family policy.
Keywords: 330; Three-child policy; total fertility rate; demographic dividend; old-age dependency ratio; total dependency ratio; pension reform